2014
DOI: 10.1371/journal.pone.0100816
|View full text |Cite|
|
Sign up to set email alerts
|

The MyD88+ Phenotype Is an Adverse Prognostic Factor in Epithelial Ovarian Cancer

Abstract: The prognosis of epithelial ovarian cancer is poor in part due to the high frequency of chemoresistance. Recent evidence points to the Toll-like receptor-4 (TLR4), and particularly its adaptor protein MyD88, as one potential mediator of this resistance. This study aims to provide further evidence that MyD88 positive cancer cells are clinically significant, stem-like and reproducibly detectable for the purposes of prognostic stratification. Expression of TLR4 and MyD88 was assessed immunohistochemically in 198 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
3
39
0
Order By: Relevance
“…More recently MyD88 protein expression was shown to be a significantly poor factor in EOC by our group and others [49,62]. …”
Section: While It Has Been Observed That Tlr-4 Expression Is Ubiquitomentioning
confidence: 70%
See 1 more Smart Citation
“…More recently MyD88 protein expression was shown to be a significantly poor factor in EOC by our group and others [49,62]. …”
Section: While It Has Been Observed That Tlr-4 Expression Is Ubiquitomentioning
confidence: 70%
“…The TLR4 gene is a validated target of the let-7i miRNA and our group has just recently demonstrated that overexpression of TLR4/MyD88 is an adverse prognostic marker in ovarian cancer [49]. We have shown that overexpression of TLR4 and MyD88 results in a shorter progression free survival and overexpression of MyD88 in a shorter overall survival.…”
Section: Discussionmentioning
confidence: 87%
“…The s2.IMM subtype showed significant up-regulation of antigen presentation machinery (e.g. TAP1 , PSMB8 and PSMB9 ); and its top subtype marker TAP1 was highly correlated with expression of PD-L1 (R Spearman = 0.72; p < 2.2E-16, Supplementary Figure 18), a marker has recently been associated with increasing tumor infiltrating T-cells and favorable prognosis in HGSOC (30). Finally, our analysis involving unsupervised clustering showed that the TGF-beta pathway is up-regulated in the mesenchymal subtype (q-value=1.5 x 10 −4 , Supplementary Table 13), which carries a worse prognosis (Figure 2A).…”
Section: Resultsmentioning
confidence: 98%
“…A few prior investigations demonstrated that high expression of either TLR4 or MyD88 in EOC tissues is associated with poor survival rates [8, 9, 21]. However, these studies failed to examine the prognostic importance of combined expression of TLR4 and MyD88, as suggested by in vitro studies.…”
Section: Discussionmentioning
confidence: 99%